Temporary Cross-clamping of the Infrarenal Abdominal Aorta During Cesarean Hysterectomy to Control Operative Blood Loss in Placenta Previa Increta/Percreta - Min-Min Chou; Yu-Min Ke; Huey-Chun Wu; Ching-Pei Tsai; Esther Shih-Chu Ho; Hamizah Ismail; Jose M. Palacios Jaraquemada (Elsevier, 2010)
Objective: To evaluate the efficacy and safety of temporary cross-clamping of the infrarenal abdominal aorta for controlling operative blood loss during cesarean hysterectomy in severe invasive placentation. Case Report: A 35-year-old woman with a significant risk factor of four previous cesarean sections and placenta previa was referred to Taichung Veterans General Hospital with suspected abnormal placentation at 37 weeks of gestation. Obstetric ultrasonography and magnetic resonance imaging showed a bulky inhomogeneous placenta with extensive uterine serosa-bladder interface hypervascularity and suspicious focal bladder invasion. Cesarean hysterectomy was performed with the use of temporary cross-clamping of the infrarenal abdominal aorta. The duration of aortic cross-clamping was 1 hour, and the estimated blood loss was 2,000 mL. The patient was discharged home on postoperative day 11 with no postoperative sequelae. Conclusion: With this limited experience, we are encouraged by the apparent reduction in operative blood loss after the use of temporary cross-clamping of the infrarenal abdominal aorta during cesarean hysterectomy. Further investigation is needed to determine the efficacy and safety of this procedure.